Endoplasmic reticulum stress and autophagy contributed to cadmium nephrotoxicity in HK-2 cells and Sprague-Dawley rats - Li, Jian-Ri; Ou, Yen-Chuan; Wu, Chih-Cheng; Wang, Jiaan-Der; Lin, Shih-Yi; Wang, Ya-Yu; Chen, Wen-Ying; Liao, Su-Lan; Chen, Chun-Jung (Food and chemical toxicology, 2020)
Excessive accumulation of cadmium is known to cause nephrotoxicity by targeting renal proximal tubular epithelial cells. Studies showed an essential role of autophagy in cadmium-induced nephrotoxicity; however, its underlying mechanisms accompanied by autophagy are incompletely understood. Using an HK-2 human renal proximal tubular epithelial cell line as a study model, sustained exposure of cadmium chloride (CdCl2) was shown to cause cell viability loss, which was alleviated by inhibitors of autophagy but not apoptosis. Data from molecular and biochemical studies revealed an induction of autophagy proteins, intracellular acidic vesicles, and autophagic flux in CdCl2-treated cells. However, there was little sign of apoptosis-related changes. Pharmacological and genetic studies indicated an elevation of Endoplasmic Reticulum (ER) stress, Forkhead Box Class O (FoxO3a), Bcl-2 Interacting Protein 3 (Bnip3), and Beclin1, as well as their involvement in cadmium-induced autophagy and autophagic cell death. Renal injury, histological changes, and molecular marker of ER stress, FoxO3a, Bnip3, and autophagy were observed in the kidney cortex of CdCl2-exposed Sprague-Dawley rats. These observations indicate that ER stress, FoxO3a, Bnip3, and autophagy signaling were actively involved in cadmium-induced nephrotoxicity. Additionally, FoxO3a may act as a linking molecule to convey ER stress signals to Bnip3 and autophagy machinery upon cadmium exposure. [Display omitted] •Cadmium causes autophagic cell death in HK-2 cells and kidney of exposed rats.•Cadmium induces ER stress and increases FoxO3a, Beclin1, and Bnip3 expression.•Inhibitors of ER stress alleviate cadmium-induced FoxO3a, Beclin1, and Bnip3 expression and autophagy.•FoxO3a silencing alleviates cadmium-induced Beclin1 and Bnip3 expression and autophagy.